Multihoming in the market for payment media: Evidence from young Finnish consumers - Ari Hyytinen; Tuomas Takalo (The Research Institute of the Finnish Economy (ETLA), 2004)
We aim at explaining why some consumers use only one medium when paying for their point-of-sale transactions, while others multihome and use many. Using data on young Finnish consumers, we find that one key determinant of multihoming behavior in the market for payment media is consumer awareness. Our instrumental variable estimates indicate that the better informed use 1.2-1.3 times more payment media than the less informed. Because many payment method innovations are typically first used simultaneously with the established methods, our results suggest that increasing consumer awareness could significantly speed up the adoption of new means of payment, such electronic money and mobile payments. – – Tässä tutkimuksessa tarkastellaan sitä, miksi jotkut kuluttajista käyttävät vain yhtä maksuvälinettä ja toiset kuluttajat monia maksuvälineitä maksaessaan päivittäisiä ostoksiaan. Käyttämällä aineistoa nuorista suomalaisista kuluttajista löydämme, että yksi tärkeimmistä maksuvälineiden käyttöön vaikuttavista tekijöistä on kuluttajien yleinen tietoisuus maksamiseen liittyvistä kysymyksistä. Instrumenttimuuttujaestimoinnit osoittavat, että paremmin tietoiset kuluttajat käyttävät 1.2-1.3 kertaa useampaa maksuvälinettä kuin vähemmän tietoiset kuluttajat. Koska monia uusia maksuvälineitä käytetään usein aluksi olemassa olevien maksuvälineiden rinnalla, tuloksemme tukevat näkemystä, että kuluttajien ietoisuuden lisääminen maksamisesta ja maksuvälineistä voisi nopeuttaa uusien maksuvälineiden, kuten elektronisen rahan ja mobiilien maksuvälineiden, käyttöönottoa. – Maksuvälineet ; kuluttajien tietoisuus ; maksuvälineiden käyttöönotto
Keywords: G20; E59; 330; Payment media; multihoming; consumer awareness; adoption of financial technology; Bargeldloser Zahlungsverkehr; Finnland